Investigation and analysis of the radiation protection status of radiation workers during the peri-pregnancy period - Liang, Binghua; Ji, Xiaojian; Zhang, Tao; Zhou, Xiang; Yu, Ziyao; Sun, Jianwei (Frontiers in Public Health, 2025)
ObjectiveRadiation exposure during pregnancy poses serious risks to fetal health, including increased likelihood of miscarriage, preterm birth, congenital anomalies and developmental disorders, while also impacting maternal occupational safety. This study aimed to assess the concerns and needs of radiation practitioners regarding radiation exposure during the perinatal period, with a focus on radiation protection.MethodsA questionnaire survey of 147 radiation practitioners from public and private hospitals was conducted to assess their knowledge, concerns and needs regarding radiation protection during the peri-pregnancy period. Statistical analysis was used to compare the importance and implementation of radiation protection in different groups, and chi-squared tests were used to compare differences in policy implementation (public vs. private hospitals), attitudes toward radiation avoidance (male vs. female practitioners) and concerns about fetal exposure across age groups.ResultsPublic hospitals demonstrated higher rates of radiation protection policies (39.37%) than private hospitals (21.43%). Among female respondents, 95.12% advocated for temporary removal from radiation-related positions when preparing for pregnancy. Of those who gave birth while working in radiation fields, 26.53% ceased radiation work pre-pregnancy, 30.61% avoided it post-pregnancy and 42.85% did not avoid it. Additionally, 86.58% of female respondents emphasized the need to avoid radiation work during breastfeeding. Among the male participants, 47.83% expressed concern about radiation effects on their fetuses compared with 90% of the female participants.ConclusionRadiation protection measures were more effectively implemented in public hospitals than in other institutions, underscoring the need for standardized policies across all institutions. Female practitioners exhibited heightened concerns about radiation exposure of the fetus and infant, particularly during pregnancy and lactation. Strengthening policies and workplace adjustments are critical to mitigating occupational risks and safeguarding maternal and child health.